PERCEPTIONS OF FINAL-YEAR STUDENTS AT UIN DATOKARAMA PALU IN UNDERSTANDING THE POSITION OF THEORY IN QUALITATIVE RESEARCH - Rustina, Rustina; M. Hidayat, (Idaarah: Jurnal Manajemen Pendidikan, 2023)
This research aims to find out the perceptions of final-year students at UIN Datokarama Palu in understanding the position of theory in qualitative research. The research uses qualitative methods with a phenomenological approach, the instrument in this research is the researcher himself, the data sources in the research are primary data originating from interviews and observations as well as secondary data originating from literature studies either sourced from journals or books related to the research objectives. submitted. The data collection technique was carried out through Focus Group Discussion (FGD) activities. After the data was collected, the next step was data analysis to produce conclusions. As for the conclusions from the results of this research, it is known that a small number of final-year students at UIN Datokarama Palu who were FGD participants quite understand the position of theory in qualitative research and can articulate or mix theory into narrative form accompanied by examples. Meanwhile, the rest have only reached the stage of understanding and are not yet able to articulate or formulate theories into narrative form accompanied by examples. This lack of ability is closely related to the interest in reading and writing by final year students who participated in the FGD. From this information, Indonesian language course lecturers and research methodology lecturers must collaborate in taking effective steps in teaching courses that can support the completion of final assignments or theses.